2015
DOI: 10.1063/1.4905202
|View full text |Cite
|
Sign up to set email alerts
|

Percolation on interacting networks with feedback-dependency links

Abstract: When real networks are considered, coupled networks with connectivity and feedback-dependency links are not rare but more general. Here, we develop a mathematical framework and study numerically and analytically the percolation of interacting networks with feedback-dependency links. For the case that all degree distributions of intra- and inter- connectivity links are Poissonian, we find that for a low density of inter-connectivity links, the system undergoes from second order to first order through hybrid pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In 2013, Zhou et al [48] researched the percolation phenomena of similar interdependent networks. In 2015, Dong et al [49] and others delved into the percolation problem of the interdependent network with feedback dependent edges and found that in the case of strong coupling, the system with feedback dependent edges is more vulnerable.…”
Section: Percolation Eorymentioning
confidence: 99%
“…In 2013, Zhou et al [48] researched the percolation phenomena of similar interdependent networks. In 2015, Dong et al [49] and others delved into the percolation problem of the interdependent network with feedback dependent edges and found that in the case of strong coupling, the system with feedback dependent edges is more vulnerable.…”
Section: Percolation Eorymentioning
confidence: 99%
“…And, they found an interesting phase transition phenomenon, hybrid transition, where the size of giant component both shows abrupt and continuous transition as attacking strength increases [70]. This mixed coupling pattern has not only inter-network interdependence but also includes inter-network connectivity to describe the coupling pattern of real-world scenario [71]. With the development and popularization of the Internet of Things, all things will be interconnected in the near future, where there exists the physical structure of interdependence, and at the same time there exists the interconnected property.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of the feedback conditions on the robustness of the multilayer network was not explained in this paper. Many real-world networks including infrastructure systems rarely appear in isolation, but always are coupled together, usually with feedback conditions [45]. [45,46] assessed the effect of feedback conditions (also called feedback dependency links) concluding that they can make multilayer networks more vulnerable.…”
Section: E Feedback Conditionsmentioning
confidence: 99%